(3ahGFO HOjYI JJYdb HShQg bd jG CjgG GdcGaQhfs
(3ChdgG (B:s
(3GdChdi EdGeG def dG jYbd hYOe ai bhdg dG CYHO eGJYHOhf heG HYOgG NeSI CLhHI , ChdgG CfgG Ci eG hbYJ Ydi eYHhOg s
(3BNQgG (B:s
(3Pdc aVd Gddg jgHg ef jTGA hGddg Ph GdaVd GdYXje hgPG GdaVd GdhSW dYGe ef YfOg Edi eG hQGgG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B13s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3eLGejY s
Keywords: (3GdeLGejYs